(untitled) (Bangladesh Journal of Pharmacology, 2015)
This randomized double-blind placebo-controlled trial was conducted on 41 patients with non-alcoholic fatty liver disease. Patients in intervention group received 100 mg/day coenzyme Q10 (CoQ10) for four weeks. There was a significant reduction in waist circumference and aspartate aminotransferase concentrations after CoQ10 supplementation (p<0.05). Dietary fiber was in negative correlation with change in serum alanine aminotransferase (ALT) concentrations (r = -410, p = 0.04), and dietary fat intake was in positive relation with serum triglyceride (r = 463, p = 0.04) and in negative relation with serum high-density lipoprotein cholesterol (HDL-C) (r = -533, p = 0.02) in CoQ10-treated group. CoQ10 supplement is able to reduce central obesity and improve liver function in non-alcoholic fatty liver disease. Dietary factors were also significant determinants of change in liver-specific enzyme ALT and lipid profile in these patients. Further trials with higher dose of CoQ10 and longer treatment periods are warranted to better clarify these findings.